A seismometric study of the Russian Nuclear Explosion on 30 October 1961 - SAHA, B. P. (MAUSAM, 1962)
Tandon (1961) has reported recently the recording of the surface waves by the long period Press-Ewing seismographs at Delhi and has made available some items of information. This had led t he writer to examine the Shillong records in the light of the above in-formation. In the past. this station has recorded seismic P-waves from a number of explosions in the Pacific (Tandon 195S). In the case of the above Russian explosion it has been possible only to record the surface waves at Delhi but apparently no P-wave has been reported. This is quite reasonable as the ex-plosion was in the upper atmosphere when on account of atmosphere-crust coupling, most of the energy incident at the surface of the earth is likely to be concentrated in the crust and would propagate as surface waves.